Risk Factors for The Incidence of Acute Respiratory Infection (ARI) in Toddlers in The Working Area of Tarus Primary Health Center, Kupang District - Olang, Eka Sukma Kumala Dewi; Adu, Apris A.; Purnawan, Sigit (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2024)
AbstractIntroduction: ARI is an acute infection that attacks one or more parts of the respiratory tract, from the nose to the deep tissues of the lungs. The number of ARI in toddlers in the Tarus primary health center in 2020 was 1.352 people and in 2021 there was a decrease of 97 people recorded, in January 2022 to February 2023, the number of ARI in toddlers increased by 1.141 cases.Methods: This research used a case-control study design. The case group is toddlers who experience ARI events, while the control group is toddlers who do not experience ARI events. The total population of toddlers in the Tarus Primary Health Center for the period January 2022 to February 2023 was 5,370 toddlers with a case group population of 1,141 toddlers and a control group population of 4,229 toddlers. The sample obtained for the case group was 117 toddlers and for the control group was 117 toddlers with a total of 234 samples.Results: The results showed no significant relationship between age (p=1.000; OR=1.000), and gender (p=0.428; OR=0.738) with the incidence of ARI in toddlers. There was a significant relationship between immunization status (p=0.000; OR=25.143), exclusive breastfeeding history (p=0.000; OR=25.016), house occupancy density (p=0.000; OR=15.416), house ventilation (p=0.000; OR=9.079) and smoking habits of family members (p=0.000; OR=9.775) with the incidence of ARI in toddlers.Conclusion : The incidence of ARI in toddlers can occur due to several risk factors such as immunization status, exclusive breastfeeding history, house occupancy density, house ventilation, and smoking habits of family members